Vibration-mediated Kondo transport in molecular junctions: conductance evolution during mechanical stretching - Rakhmilevitch, David; Tal, Oren (Beilstein Journal of Nanotechnology, 2015)
The vibration-mediated Kondo effect attracted considerable theoretical interest during the last decade. However, due to lack of extensive experimental demonstrations, the fine details of the phenomenon were not addressed. Here, we analyze the evolution of vibration-mediated Kondo effect in molecular junctions during mechanical stretching. The described analysis reveals the different contributions of Kondo and inelastic transport.
Keywords: correlated systems; electron–phonon interactions; Kondo effect; molecular junctions; vibrations